ʺPreparation of future teachers for the application of distance learning technology in the educational environmentʺ - Babakina, O.; Lytvyn, V. (Problems of Engineer-Pedagogical Education, 2022)
The article characterizes the specifics of training future teachers to use distance learning technology in the educational process. It was found that information technologies in the educational process are implemented quite dynamically, and therefore the method of their use should be developed in the same way. It is important for modern teachers not only to be fluent in their subject area, but also to be highly qualified professionals who are fluent in digital technologies that are directly related to their professional activities. It was determined that distance learning is learning in a virtual educational space, in the process of which students can be located at great spatial distances from each other and exchange messages both among themselves and with teachers using an electronic network; distance learning technology is a set of methods, techniques, forms, means and tools that are implemented in the educational process in order to effectively carry out pedagogical activities aimed at achieving the goals of distance learning. The generalization of opinions of domestic and foreign scientists helped to identify trends in the development of distance learning technologies in higher pedagogical education. Such trends include: 1) increasing the role of distance learning technologies through innovative information and communication technologies, which are a guarantee of the effectiveness of distance learning technology; 2) development and introduction into the educational process of distance learning technologies which are aimed at the personality of students, contribute to the motivation for educational and cognitive activities, provide a variable and corrective nature of the educational process. It was proved that training future teachers to use distance learning technology in the educational process will be effective as a result of using information and communication technologies in the educational process, working in an open computer-oriented educational environment and applying distance learning technologies in vocational training.